2019
DOI: 10.1002/mame.201900263
|View full text |Cite
|
Sign up to set email alerts
|

Impact Optimization of 3D‐Printed Poly(methyl methacrylate) for Cranial Implants

Abstract: Material extrusion‐based additive manufacturing, also known as fused filament fabrication (FFF) or 3D printing facilitates the fabrication of cranial implants with different materials and complex internal structures. The impact behavior plays a key role in the designing process of cranial implants. Therefore, the performance of impact tests on novel implant materials is of utmost importance. This research focuses on investigating the dependency of the infill density and pattern on the impact properties of 3D‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…Additionally, by altering the ratio of soft and hard segments, a wide selection of TPUs with different mechanical properties, mostly represented by varying hardness values, are available depending on the desired application. A broad mechanical portfolio is beneficial for employing TPUs as IDDS, as not only the biomechanical properties of implants need to be as similar as possible to the properties of the adjacent tissue [ 36 , 53 ], but also the drug release rates can be influenced by the ratio of soft to hard segments [ 54 ]. Recent studies have confirmed the great potential of non-biodegradable TPUs to deliver various APIs from IDDS [ 54 , 55 , 56 ] and vaginal rings [ 57 , 58 , 59 , 60 ] but also as matrix excipients in oral tablets [ 49 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, by altering the ratio of soft and hard segments, a wide selection of TPUs with different mechanical properties, mostly represented by varying hardness values, are available depending on the desired application. A broad mechanical portfolio is beneficial for employing TPUs as IDDS, as not only the biomechanical properties of implants need to be as similar as possible to the properties of the adjacent tissue [ 36 , 53 ], but also the drug release rates can be influenced by the ratio of soft to hard segments [ 54 ]. Recent studies have confirmed the great potential of non-biodegradable TPUs to deliver various APIs from IDDS [ 54 , 55 , 56 ] and vaginal rings [ 57 , 58 , 59 , 60 ] but also as matrix excipients in oral tablets [ 49 , 61 , 62 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the elongation at break of the linear and diagonal was not significantly different and the hexagonal infill was significantly lower [53]. For PMMA specimens, it was observed that the 3D honeycomb infill pattern outperforms the rectilinear and gyroid infill patterns for infill densities from 30% to 70% when referring to impact resistance [54]. Therefore, selecting the infill parameters depends on the application of the part.…”
Section: Rectilinearmentioning
confidence: 99%
“…Common implant materials are polymethylmethacrylate (PMMA), polyetheretherketone (PEEK), polyethylene, hydroxyapatite, and titanium (Kwarcinski et al, 2017 ). PEEK delivers the most satisfactory results for large‐sized cranial defects, especially considering its physical and mechanical characteristics (strength, stiffness, durability) and its suitability for 3D printing (Mohan et al, 2016 ; Petersmann et al, 2019 ). PMMA is characterized by its obtainability, processability, and affordability, rendering it one of the most frequently used materials for implant design.…”
Section: Introductionmentioning
confidence: 99%